The Lady Doc - Lockhart, Caroline, 1870-1962; Hoskins, Gayle Porter, 1887-1962 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Lady Doc" by Caroline Lockhart is a novel written in the early 20th century. The book explores the lives of two strong women$1 (BDr. Emma Harpe, a doctor contending with the consequences of a surgical mistake, and Essie Tisdale, a waitress navigating her way through small-town romance and ambition. Set against the backdrop of a burgeoning frontier town, the story delves into themes of resilience, social dynamics, and the pursuit of identity in a rugged environment. At the start of the novel, we are introduced to Dick Kincaid, a youthful prospector who stumbles upon a tragic scene involving two starving children and their mother in a desolate cabin. This visual sets a grim tone, reflecting the harsh realities of frontier life. As Kincaid assists the children, the narrative shifts to Dr. Harpe two decades later, portraying her struggles as a female physician facing professional and personal turmoil. Simultaneously, Essie Tisdale's vibrant character embodies the hopeful spirit of the town of Crowheart, where dreams collide with harsh truths. The intricate interweaving of Kincaid$1 (Bs discovery, Dr. Harpe's ambition, and Essie's lively presence hints at the broader exploration of community, survival, and the distinctive challenges women face in a masculine world. The opening chapters effectively establish a gripping context for the stories that will unfold, showcasing the struggles and triumphs of life on the frontier. (This is an automatically generated summary.)s
Release date is 2007-11-03
E-text prepared by Roger Frank and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net)
Keywords: Women physicians -- Fiction